Master passions : emotion, narrative, and the development of culture - Moldoveanu, Mihnea C. (MIT Press, 2002)
An exploration of the powerful role of anxiety, ambition, and envy in shaping both our individual lives and society as a whole. At the heart of the human experience lies anxiety caused by the realization that the world is unknown, forever eluding our control. And out of this anxiety arises the master passions of ambition and envy, which we repress to mask their power over our lives. Discussion of the role of the emotions in our lives is not new, but Mihnea Moldoveanu and Nitin Nohria go much further, showing how these passions shape not only our individual lives but our social and organizational culture as well. The master passions are not pretty, and so we cover them with the more socially acceptable faces of reason and morality. Moldoveanu and Nohria guide the reader in revealing the real impetus behind such actions as firing a friend, leaving a lover, or even pillaging your own people. Below the rational explanation, they show, often lies a willingness to hurt or even destroy others to fuel our own ambitions or quench the fires of envy. The authors offer intriguing thought experiments and examples from their own lives as they expose the power of the master passions. Deftly weaving ideas from psychology (Sigmund Freud), sociology (Max Weber), literature (William Shakespeare, Albert Camus), and philosophy (David Hume, Adam Smith, Karl Marx, Friedrich Nietzsche) with the personal, they build a strong argument that society would be much healthier if we faced the deception and self-deception that pervade our lives.